1992
DOI: 10.1007/bf00055603
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter comparison of nicorandil and diltiazem on serum lipid, apolipoprotein, and lipoprotein levels in patients with ischemic heart disease

Abstract: The effects of nicorandil and diltiazem on serum lipid, apolipoprotein, and lipoprotein levels in 37 patients with ischemic heart disease were examined in a randomized, multicenter study. Nicorandil (n = 20, 10-40 mg/day, b.i.d.) and diltiazem (n = 17, 60-240 mg/day, b.i.d.) were administered for 12 weeks. Both nicorandil and diltiazem administration showed an effective antianginal effect. Diltiazem administration showed a significant hypotensive action. There were no significant changes in serum lipids, apoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…However, in one study after changing from HCTZ to verapamil the SUA level fell significantly (p < 0.001) from 5.5 ± 1.2 to 4.2 ± 0.8 mg/dl (0.33 ± 0.07 to 0.25 ± 0.05 mmol/l) [76]. Some but not all studies showed that diltiazem can reduce SUA levels [77][78][79][80][81]. This effect may be partly mediated by diminishing urate production [81].…”
Section: Calcium Channel Blockersmentioning
confidence: 98%
“…However, in one study after changing from HCTZ to verapamil the SUA level fell significantly (p < 0.001) from 5.5 ± 1.2 to 4.2 ± 0.8 mg/dl (0.33 ± 0.07 to 0.25 ± 0.05 mmol/l) [76]. Some but not all studies showed that diltiazem can reduce SUA levels [77][78][79][80][81]. This effect may be partly mediated by diminishing urate production [81].…”
Section: Calcium Channel Blockersmentioning
confidence: 98%
“…It acts as a balanced coronary and peripheral vasodilator, and reduces both preload and afterload in patients with coronary artery disease. In several randomized controlled trials, nicorandil has demonstrated equivalent efficacy to nitrate, beta blockers and calcium channel blockers in relieving symptoms of angina …”
mentioning
confidence: 99%
“…To the best of our knowledge, the risk of GI ulceration/perforation among nicorandil users has not previously been examined in a large general population. Several randomized controlled trials (RCT) have shown nicorandil to be an effective and safe drug in relieving angina symptoms 20 21 22 23 24 25 26 27 28 29 39 . These RCTs, however, did not associate mucosal and cutaneous ulcerations with nicorandil treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological properties of nicorandil came from the nicotinamide ester, which can result in vasodilation of arteries and veins. In several randomized controlled trials, nicorandil has demonstrated equivalent efficacy to nitrate, calcium channel blockers, and beta-blockers in relieving angina symptoms 20 21 22 23 24 25 26 27 28 29 . Unfortunately, these randomized controlled trials did not monitor gastrointestinal (GI) ulceration or perforation as one of the adverse effects.…”
mentioning
confidence: 99%